Characteristics of distinct ash flows in a biomass thermal power plant with bubbling fluidised bed combustor. (October 2015) - Tarelho, L.A.C.; Teixeira, E.R.; Silva, D.F.R.; Modolo, R.C.E.; Labrincha, J.A.; Rocha, F.
Abstract: Characteristics of biomass used as fuel and distinct ash flows in a thermal power plant with BFBC (bubbling fluidised bed combustion) technology were studied. An integrated approach involving chemical composition, microscopy analysis, mineralogy, and thermal behaviour were used to characterize the ash. The ashes have a low unburned content, typically below 3 wt.% (dry basis), with higher values in ash from the electrostatic precipitator. The chemical element present in higher concentration in the several ash flows is Si (>20 wt.%, dry basis). The fly ash from the electrostatic precipitator are enriched in heavy metals when compared to other ash, and Zn is the heavy metal found in higher concentration (but <225 ppm wt., dry basis), followed by Cr, Pb, Cu and Ni in decreasing order of abundance. The distinct ash produce leaching solutions with pH values in range 11.9–12.8, and conductivity in the range 4.7–19.5 mS/cm, with higher values in ash from electrostatic precipitator. Ca is the element in higher concentration in the ash leachates, followed by K, Na and Cl. The concentration of heavy metals in the leachates is relatively low. The biomass quality influences the ash characteristics, and an appropriate management of biomass and ash is need to improve the performance of thermal power plants. Highlights: Forest biomass properties influence its quality as fuel and thermal plant performance. Chemical composition, mineralogy, thermal behaviour are important ash analysis tools. Fly ash at diverse points in a thermal plant are distinct, and differ from bottom ash. Distinct ashes in a thermal plant must be managed according to their characteristics.